2020
DOI: 10.1101/2020.08.24.256560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

αKG inhibits Regulatory T cell differentiation by coupling lipidome remodelling to mitochondrial metabolism

Abstract: The differentiation of CD4 T cells to a specific effector fate is metabolically regulated, integrating glycolysis and mitochondrial oxidative phosphorylation (OXPHOS) with transcriptional and epigenetic changes. OXPHOS is tightly coordinated with the tricarboxylic acid (TCA) cycle but the precise role of TCA intermediates in CD4 T cell differentiation remain unclear. Here we demonstrate that α-ketoglutarate (α-KG) inhibited regulatory T cell (Treg) generation while conversely, increasing Th1 polarization. In a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 128 publications
0
2
0
Order By: Relevance
“…Mitochondrial GLUD1, another P5 target, is known to play key role in replenishing tricarboxylic acid (TCA) cycle intermediate a-ketoglutarate from L-glutamate (48). a-Ketoglutarate performs crucial role in T-cell differentiation (49). Furthermore, GLUD1 enzyme plays an important role in insulin balance (50) and is one of the top candidates that is involved in long term memory and spatial learning (51).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial GLUD1, another P5 target, is known to play key role in replenishing tricarboxylic acid (TCA) cycle intermediate a-ketoglutarate from L-glutamate (48). a-Ketoglutarate performs crucial role in T-cell differentiation (49). Furthermore, GLUD1 enzyme plays an important role in insulin balance (50) and is one of the top candidates that is involved in long term memory and spatial learning (51).…”
Section: Discussionmentioning
confidence: 99%
“…Supplying a-ketoglutarate altered the methylation pattern of naïve CD4+ T cells activated under T reg polarizing conditions, which led to reduced T reg differentiation and decreased FOXP3 expression among adoptively transferred cells. These investigators suggested that a-ketoglutarate reprograms T cells to increase mitochondrial metabolism, which may affect the fate of CD4+ T-cell (specifically, T reg ) differentiation (212). Further research into the intersection of DNA methylation patterns and Tcell metabolism is warranted to inform a stronger mechanistic understanding of how this intersection can be therapeutically harnessed..…”
Section: Methylationmentioning
confidence: 99%